Intraocular pressure in children after congenital heart surgery: A single-center study - Sunali Goyal; Paul H Phillips; Lamonda A Corder; Michael J Robertson; Xiomara Garcia; Michael L Schmitz; Punkaj Gupta (Wolters Kluwer Medknow Publications, 2017)
Background: The impact of varied cardiac physiologies on intraocular pressure (IOP) among children undergoing heart operations is unknown. Aim: The aim of this study was to determine the IOP among children with varying cardiovascular physiologies and varying hemodynamics after their heart operation. Setting and Design: This was a prospective, observational study. Materials and Methods: Patients ≤18 years undergoing congenital heart surgery were included in this study. IOP measurement was performed by Icare® tonometer between 3 and 14 days after heart operation. Statistical Analysis: Summary statistics were estimated for all demographic, anthropometric, and clinical data. Results: A total of 116 eyes from 58 children were included. The mean and standard deviation age was 28.4 (45.8) months. Single-ventricle anatomy was present in 26 patients (45%). Despite similar heart rate and blood pressure, the mean IOP among the patients with single-ventricle anatomy was significantly elevated as compared to patients with two-ventricle anatomy (18 mm Hg vs. 12 mm Hg, P < 0.001). There was no difference in IOP measurements based on the complexity of operation performed. We noted that patients undergoing surgical palliation with central shunt (21 mm Hg), Fontan operation (19 mm Hg), bidirectional Glenn operation (19 mm Hg), Norwood operation (19 mm Hg), or definitive repairs such as tetralogy of Fallot repair (17 mm Hg), and atrioventricular canal repair (19 mm Hg) were associated with the highest IOPs in the study cohort. Conclusions: This study demonstrates that IOPs vary with varying cardiovascular physiology after pediatric cardiac surgery.